2012
DOI: 10.1136/bmjqs-2012-001215
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the missing pieces between the hospital and primary care: mapping the patient process during care transitions

Abstract: Background: Safe patient transitions depend on effective communication and a functioning care coordination process. Evidence suggests that primary care physicians are not satisfied with communication at transition points between inpatient and ambulatory care, and that communication often is not provided in a timely manner, omits essential information, or contains ambiguities that put patients at risk. Objective: Our aim was to demonstrate how process mapping can illustrate current handover practices between am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 23 publications
2
64
0
Order By: Relevance
“…79 Process mapping was also a key tool for understanding the discharge process as part of the HANDOVER project funded by the European Union. 80 The purpose of the familiarisation phase was to enable the researcher to build an initial understanding of the flow of activities, and to identify suitable staff roles for participation in the subsequent process mapping session.…”
Section: Systematic Description Of Clinical Handover Within the Emergmentioning
confidence: 99%
“…79 Process mapping was also a key tool for understanding the discharge process as part of the HANDOVER project funded by the European Union. 80 The purpose of the familiarisation phase was to enable the researcher to build an initial understanding of the flow of activities, and to identify suitable staff roles for participation in the subsequent process mapping session.…”
Section: Systematic Description Of Clinical Handover Within the Emergmentioning
confidence: 99%
“…It has been suggested that primary care phsicians are not satisified with communication at transition points because communication is not provided in a timely manner, omits essential information, or contains ambiguities that put patients at risk (Johnson, et al, 2012;Kripalani, LeFevre, Phillips, Williams, Basaviah, & Baker, 2007). This can be seen in KCH and shows the need for the AEU to have a standardized data collection form that omits the ambiguties and contains questions to receive the essential information quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Another study performed by Johnson et al used clinical teams from six countries to create a process map and determine the missing pieces during care transitions (2012). The process map showed them similar barriers to providing information to primary care physicians, inaccurate or incomplete information on referral and discharge, problems with collaboration with counterpart colleagues, and lack of feedback to clinicians involved in the handovers (Johnson et al, 2012). were performed in six academic health centers around the world in a study aimed to demonstrate how process mapping could 1) illustrate handover practices between ambulatory and inpatient care settings, 2) identify barriers and facilitators to effective transitions of care, 3) and identify areas for quality improvement (Johnson, et al, 2012 …”
Section: Process Mappingmentioning
confidence: 99%
See 2 more Smart Citations